Acrobustitis-phimosis in bulls: postoplasty technique performed with the animals in a standing position - Lopes, Monike Alves [UNESP]; Papa, Frederico Ozanam [UNESP] (FapUNIFESP (SciELO), 2023)
Acrobustitis is the inflammation of the distal prepuce, which can lead to a narrowing of the preputial ostium due to stenosis or growth of fibrous tissue after an inflammatory reaction. This condition usually occurs in cattle with long prepuce, such as Zebu or Zebu’s crossbreeds, leading the animal to Impotentia Coeundi, this condition is characterized by the bull's disability to copulate, that leads to lower herd fertility and consequent financial losses. Normally, corrective surgeries are performed on-farm and the animal is placed in a lateral recumbency. However, in some situations the animal is restrained with ropes and remains on the grass, dirt or even on uneven floors, which can cause neuropathies, bloat or hypoxia. Due to a series of complications that can occur in the postoperative period of surgery in the lateral recumbency, this article aims to describe the surgical technique for correcting acrobustitis with the animal in a standing position. Ten corrective surgeries for acrobustitis were performed in adult bulls between 4 and 8 years of age and predominantly of zebu or crossbreeds, with a total recovery of the animals for full reproductive activity.
Keywords: acrobustitis surgery; acroposthitis; impotentia coeundi